Embodied Semantics in a Second Language: Critical Review and Clinical Implications - Monaco, Elisa; Jost, Lea B.; Gygax, Pascal M.; Annoni, Jean-Marie (Frontiers in Human Neuroscience, 2019)
The role of the sensorimotor system in second language (L2) semantic processing as well as its clinical implications for bilingual patients has hitherto been neglected. We offer an overview of the issues at stake in this under-investigated field, presenting the theoretical and clinical relevance of studying L2 embodiment and reviewing the few studies on this topic. We highlight that a) the sensorimotor network is involved in L2 processing, and that b) in most studies, L2 is differently embodied than L1, reflected in a lower degree or in a different pattern of L2 embodiment. Importantly, we outline critical issues to be addressed in order to guide future research. We also delineate the subsequent steps needed to confirm or dismiss the value of language therapeutic approaches based on embodiment theories as a complement of speech and language therapies in adult bilinguals.